The mutagenic potential of Clusia alata (Clusiaceae) extract based on two short-term in vivo assays - Moura, A. C. G. [UNESP]; Perazzo, F. F. [UNESP]; Maistro, Edson Luis [UNESP] (Funpec-editora, 2008)
We examined the genotoxic and mutagenic effects of a crude extract of Clusia alata ( a potential medicinal plant) on peripheral leukocyte and bone marrow cells of mice, using the comet and chromosome aberration assays. Extracts at doses of 1000, 1500 and 2000 mg/kg were administered by gavage, and a positive control, N-nitroso-N-ethylurea (50 mg/kg) was injected intraperitoneally. Peripheral blood leukocytes were collected 4 and 24 h after the treatments for the comet assay, and bone marrow cells were collected 24 h after the treatments, for the chromosome aberration assay. The comet assay showed that C. alata extract causes an increase in damage to DNA in the peripheral blood leukocytes, but it was significant only with the 2000 mg/kg dose after 24 h; the extract also induced a small but significant increase in the mean number of chromosome aberrations in the bone marrow cells at doses of 1500 and 2000 mg/kg. No evidence of a significant decrease in the mitotic index was observed. Acute consumption of high concentrations of C. alata extract produced some mutagenic effects in bone marrow cells.
Keywords: Clusia alata; Comet assay; Chromosome aberrations; Single-cell gel electrophoresis